Penerapan Sistem Informasi Cashflow dan Inventory Barang Pada Bengkel Vespa Jangkar Kudus - Bintang Bahariawan; Arif Setiawan (CV. Ulil Albab Corp, 2026)
The rapid development of information technology has had a significant impact on various business sectors, including service businesses and vehicle repair workshops. The Vespa Jangkar Kudus Workshop still manages cash flow and inventory data manually, which causes various problems, such as recording errors, reporting delays, difficulties in monitoring stock, and the risk of data loss. This study aims to design and implement a web-based cash flow and inventory information system to improve operational efficiency and simplify financial and inventory data management. The community service methods used include observation, interviews, and documentation, while the system development method applied is the System Development Life Cycle (SDLC) waterfall model. The developed system has features for managing financial income and expenses, managing stock, generating reports, and providing user access rights for admins and owners. The community service results show that the implemented system is able to simplify the transaction recording process, improve the accuracy of financial and inventory data management, and support real-time data monitoring. In addition, this system also helps improve operational effectiveness and supports more appropriate decision-making in workshop management. Thus, the implementation of this web-based information system is expected to improve the quality of business management at the Vespa Jangkar Kudus Workshop.